Law against the people/The empire strikes back (Antropolítica - Revista Contemporânea de Antropologia, 2018)
George E. Bisharat Emeritus Professor of Law, University of California Hastings College of the Law. George E. Bisharat was a trial lawyer for the Office of the Public Defender in San Francisco before joining the UC Hastings faculty in 1991. Professor Bisharat studied law, anthropology, and Middle East studies at Harvard, and wrote a book about Palestinian lawyers working under Israeli military occupation in the West Bank. He writes frequently on the Middle East, both for academic audiences and for major media sources in the U.S. and abroad. After taking emeritus status in 2015, Bisharat, as “Big Harp George,” has recorded two blues albums that earned award nominations and critical acclaim. SUMMARY The objective of this article is to describe and analyze how supporters of Israeli state policies have, since 2000, used legal forms often associated with efforts by the powerless to challenge entrenched power to instead turn those forms into tools of the powerful. This movement to use “law against the people” has come about largely as a reaction against attempts by activists to use courts and other legal fora to advance Palestinian rights. This unexpected boomerang effect provides reason for reflection on the role of law in the struggle for justice in Israel/Palestine, suggesting that law offers little promise of relief, at least when it is not integrated with and supported by a broader political strategy.